Comparison of visual and ultrasound based techniques to measure head repositioning in healthy and neck-pain subjects. - Roren A; Mayoux-Benhamou M; Fayad F; Poiraudeau S; Lantz D; Revel M (Manual Therapy, 2009)
Three-dimensional (3D) ultrasound based (US) and usual Revel visual techniques were compared to measure head repositioning ability in 41 healthy subjects and 41 subjects with neck pain. Head repositioning absolute value of the global error (AE) was calculated by both techniques after active head rotations. The AE was 3.6 degrees and 3.7 degrees for healthy subjects and 6.3 degrees and 6.1 degrees for neck-pain subjects for the visual and US techniques, respectively. The AE was higher in neck-pain subjects (p<0.001), and a value of 4.5 degrees was identified as a threshold of abnormal repositioning for both techniques. The test-retest reliability, calculated in the neck-pain subjects, was moderate (intraclass correlation coefficient [ICC]=0.68) for both techniques. The correlation between the two techniques for AE was poor for both groups with successive measurement of visual and US techniques (r=0.32 and 0.46, respectively) but excellent with simultaneous measurement (r=0.95 for both groups). Moreover, we showed substantial agreement between the techniques in discriminating healthy and neck-pain subjects (kappa=0.65). The Revel visual technique is more appropriate for clinical practice, but with improved software, the 3D US method could provide additional quantitative and qualitative data invaluable for research.